In the beginning, there was general paediatrics …. (January 2015) - Gunasekera, Hasantha; Kilham, Henry
Abstract In this article, we address how general paediatrics has evolved and adapted to change over the past 50 years and speculate on its future directions. We compare the state of general paediatrics with that of general adult medicine. We argue that general paediatrics must continue to have a strong role both in paediatric teaching hospitals and the community.